The secret keeper : a novel - Morton, Kate, 1976- (New York : Atria Books, 2012)
Teenager Laurel is daydreaming in her tree house, when she sees a stranger speaking to her mother. Before the afternoon is over, Laurel will witness a shocking crime that challenges everything she knows about her family. Now, fifty years later, Laurel returns to the family farm and finds herself overwhelmed by questions she has not thought about for decades.
Keywords: Family secrets -- Fiction; Life change events -- Fiction; Actresses -- England -- Fiction; Great Britain -- Social life and customs -- 20th century -- Fiction; Mystery fiction